Effects of hydrolyzed collagen combined with resistance training on treating Achilles, patellar, and plantar fascia tendinopathy in elite athletes - Thomsen, L. L.; Olesen, A. E.; Schjerling, P.; Svensson, R.; Bisgaard, M. S.; Dideriksen, K.; Bach, J.; Hansen, E.; Trammell, S. A.; Vestergaard, M.; Karlsson, M.; Brushoj, Hølm, L.; et al. (BMJ Open Sport & Exercise Medicine, 2026)
Introduction Tendinopathy is a significant problem in elite athletes. Collagen supplementation has been shown to increase collagen synthesis, but it remains unknown whether collagen supplementation could serve as an effective add-on treatment to heavy slow resistance (HSR) training in the treatment of tendinopathy. This study investigated whether daily hydrolyzed collagen ingestion enhances HSR training outcomes compared with placebo in male elite athletes with chronic patellar, Achilles, or plantar fascia tendinopathy.